Tuberculous Spondylitis following Intravesical Bacillus Calmette-Guerin for Bladder Cancer - Masashi Miyazaki; Toyomi Yoshiiwa; Toshinobu Ishihara; Masanori Kawano; Hiroshi Tsumura (Case Reports in Orthopedics)
We present a rare case of tuberculous spondylitis following intravesical Bacillus Calmette-Guerin (BCG) therapy for bladder cancer. An 82-year-old man presented with low back pain. Past medical history revealed bladder cancer diagnosed and treated 16 months previously by intravesical BCG. Magnetic resonance imaging of the thoracic spine showed destruction of the T5 and T6 vertebrae and an epidural soft tissue mass with anterior dural sac compression. Due to the progression of vertebral destruction, posterior spinal segmental fusion was performed. Mycobacterium bovis (M. bovis) was identified using multiplex polymerase chain reaction of surgical tissue specimens. The patient was started on an antituberculosis treatment regimen including isoniazid, rifampicin, and ethambutol. After surgery, his back pain resolved completely. At the latest examination, the patient was pain-free with no functional limitations or recurrent infection in clinical or imaging findings. Patients undergoing BCG therapy should be monitored for possible hematogenous spread of mycobacteria to the spine for months or even years after treatment.